Establishment of a Multiplex RT-PCR Method for the Detection of Five Known Genotypes of Porcine Astroviruses - Liu, Xin; Zhang, Wenchao; Wang, Dongjing; Zhu, Xinyue; Chen, Ying; Ouyang, Kang; Wei, Zuzhang; Liu, Huan; Huang, Weijian (Frontiers in Veterinary Science, 2021)
Porcine astroviruses (PAstVs) are prevalent in pigs worldwide and five known genotypes have been reported to circulate in China. However, little is known about the co-infection status of PAstVs. For differential diagnosis, a multiplex RT-PCR method was established on the basis of the ORF2 gene of type 1 PAstV and the ORF1ab genes of type2~5 PAstVs. This multiplex RT-PCR could specifically detect all the five PAstV genotypes without cross-reaction to any other major viruses circulating in Chinese pig farms. The detection limit of this method was as low as 102 ng cDNA of each PAstV genotypes. A total of 275 fecal samples collected from different districts of Guangxi, China, between April 2019 and November 2020 were tested by this multiplex RT-PCR. The results revealed that PAstV1 (31/275), PAstV2 (49/275), PAstV3 (36/275), PAstV4 (41/275) and PAstV5 (22/275) were all detected, and dual (PAstV1+PAstV2, PAstV1+PAstV3, PAstV2+PAstV3, PAstV2+PAstV4, PAstV3+PAstV4, PAstV4+PAstV5) or triple genotypes (PAstV1+PAstV2+PAstV3, PAstV2+PAstV3+PAstV4) of co-infections were also unveiled in this study. This multiplex RT-PCR method offered a valuable tool for the differential diagnosis of PAstVs circulating in pig herds and will facilitate the surveillance of PAstV co-infection status.